2017
DOI: 10.1016/j.jcmg.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Severe Aortic Stenosis in the Elderly

Abstract: In elderly patients with severe but asymptomatic AS, mild symptoms may be difficult to detect, particularly when mobility is impaired and severe symptom onset is common, warranting close clinical follow-up. Furthermore, a very high event rate can be expected, and cardiac deaths are not infrequent. Thus, elective aortic valve procedures may be considered in selected elderly patients at low procedural risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…A recent study of 103 asymptomatic patients with severe AS aged >70 years reported that a Vmax ≥5 m/s was predictive of AVR or death. 24 These studies have undeniably validated Vmax as an outcome predictor in AS. However, the relationship between Vmax and survival per se has not been specifically investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 103 asymptomatic patients with severe AS aged >70 years reported that a Vmax ≥5 m/s was predictive of AVR or death. 24 These studies have undeniably validated Vmax as an outcome predictor in AS. However, the relationship between Vmax and survival per se has not been specifically investigated.…”
Section: Discussionmentioning
confidence: 99%
“…21 Initial symptoms experienced by patients with AS, who are usually elderly, are often subtle, and many patients fail to acknowledge or report their symptoms until overt heart failure presents. 22 Early AVR is debated in asymptomatic patients, and the optimal timing for AVR remains controversial because of the lack of prospective studies on the determinants of AS progression, studies on risk stratification, and patient management. 23 Because longitudinal function at rest is related to patients' prognosis, we sought to investigate the additional value of longitudinal function at exercise in patients with asymptomatic AS.…”
mentioning
confidence: 99%
“…En nuestra población se considera EA severa cuando, Las guías sobre manejo de la enfermedad valvular de la AHA/ACC (2) recomiendan como indicación clase IIA la sustitución valvular aórtica en la EA severa asintomática con FEVI conservada y VMáx ³5 m/s, en tanto la ESC la aconseja con VMáx ³5,5 m/s (1) . En un trabajo reciente, Zilberszac (15) realiza un seguimiento de 103 pacientes mayores de 70 años con EA severa asintomática. Define la EA muy severa con una VMáx ³5 m/s en base a que es un punto de corte que predice la evolución en forma independiente.…”
Section: Discussionunclassified